Diaphyseal Forearm Fractures in Children Treated with Titanium Elastic Nail System - Adhikari, Vijayendra; Mishra, Anil Kumar; Chalise, Prahlad Kumar; Shrestha, Praphulla; Singh, Ramesh Prasad (Nepal Orthopaedic Association Journal, 2019)
BACKGROUND: The common injuries in the pediatric population is the forearm fracture around the diaphyseal region. These fractures can result in functional disability, especially in older children due to angular or rotational deformity, which can be minimized by restoration of normal alignment. Titanium Elastic Nailing system is a minimally invasive procedure that spares physis, provides threepoint fixation allowing early mobilization.METHODS: The study included total of 35 children with the aim of assessing the bony union and functional outcome according to Price CT et al criteria of titanium elastic nail in diaphyseal forearm fractures.RESULTS: In this study, there were 21 boys and 14 girls with a mean age of9.8 years. Twenty-four children had right forearm fracture and 11 had left forearm fracture. Close reduction was achieved in all cases except in 6 cases where open reduction with mini incision was performed. All of the fractures clinically healed within an average of 6 weeks and radiological union was by the end of 14 weeks. The results according to Price CT et al were excellent in most of the cases. There were no patients with a poor outcome.CONCLUSION: Titanium Elastic Nailing system is a safe, effective and minimally invasive method of fixation of diaphyseal forearm fractures in children with excellent results in terms of union and functional outcomes in the majority of patients with minimal complication.